Effect of Ability, Work Life Balance, Work Satisfaction on Performance of Employees in BMT Permata-Jatim - Rochim Sidik (Alliance of Health Activists (AloHA), 2019)
The aim to be achieved in this study is to know and analyze the influence of abilities , work-life balance , job satisfaction simultaneously and significantly on employee performance at BMT Permata Jatim. The population in this study were female employees who worked at the BMT Permata Jatim Office who had worked for more than two years and those who are married ,amounting to 30 people. The test used in this study is a multiple linear regression test. Based on the results of the analysis and discussion carried out in this study, the researcher draws the following conclusions: the ability to influence the performance of employees at BMT Permata Jatim. W life balance has an effect on employee performance at BMT Permata Jatim. The extent of work affects the performance of employees at BMT Permata Jatim. Based on the results of the testing of simultaneous significance the results showed that the ability, work life balance , and job satisfaction had an effect on the performance of employees at BMT Permata-Jatim. Keywords: Ability, Work-life balance, Job satisfaction, Employee performance